5-Aza-2′-Deoxycytidine Has Minor Effects on Differentiation in Human Thyroid Cancer Cell Lines, But Modulates Genes That Are Involved in Adaptation In Vitro - Dom, Geneviève (Mary Ann Liebert, Inc., 2013)
BACKGROUND: In thyroid cancer, the lack of response to specific treatment, for example, radioactive iodine, can be caused by a loss of differentiation characteristics of tumor cells. It is hypothesized that this loss is due to epigenetic modifications. Therefore, drugs releasing epigenetic repression have been proposed to reverse this silencing. METHODS: We investigated which genes were reinduced in dedifferentiated human thyroid cancer cell lines when treated with the demethylating agent 5-aza-2′-deoxycytidine (5-AzadC) and the histone deacetylase inhibitors trichostatin A (TSA) and suberoylanilide hydroxamic acid, by using reverse transcriptase–polymerase chain reaction and microarrays. These results were compared to the expression patterns in in vitro human differentiated thyrocytes and in in vivo dedifferentiated thyroid cancers. In addition, the effects of 5-AzadC on DNA quantities and cell viability were investigated. RESULTS: Among the canonical thyroid differentiation markers, most were not, or only to a minor extent, re-expressed by 5-AzadC, whether or not combined with TSA or forskolin, an inducer of differentiation in normal thyrocytes. Furthermore, 5-AzadC–modulated overall mRNA expression profiles showed only few commonly regulated genes compared to differentiated cultured primary thyrocytes. In addition, most of the commonly strongly 5-AzadC–induced genes in cell lines were either not regulated or upregulated in anaplastic thyroid carcinomas. Further analysis of which genes were induced by 5-AzadC showed that they were involved in pathways such as apoptosis, antigen presentation, defense response, and cell migration. A number of these genes had similar expression responses in 5-AzadC–treated nonthyroid cell lines. CONCLUSIONS: Our results suggest that 5-AzadC is not a strong inducer of differentiation in thyroid cancer cell lines. Under the studied conditions and with the model used, 5-AzadC treatment does not appear to be a potential redifferentiation treatment for dedifferentiated thyroid cancer. However, this may reflect primarily the inadequacy of the model rather than that of the treatment. Moreover, the observation that 5-AzadC negatively affected cell viability in cell lines could still suggest a therapeutic opportunity. Some of the genes that were modulated by 5-AzadC were also induced in nonthyroid cancer cell lines, which might be explained by an epigenetic modification resulting in the adaptation of the cell lines to their culture conditions.